Singular Integrals and the Principal Series, II - Knapp, A. W. (1970)
A further study is made of the intertwining operators for the representations of the simple Lie groups of real rank one. We extend and apply this to the higher rank case, obtaining various results dealing with reducibility of principal series and existence of complementary series.